The myth of the stay-at-home family firm: How family-managed SMEs can overcome their internationalization limitations - Hennart, Jean-François; Majocchi, Antonio; Forlani, Emanuele (Journal of International Business Studies, 2019)
The prevalent view among family-firm internationalization scholars is that family management discourages internationalization. This is because selling abroad is said to require more specialized managers and more resources than selling at home, and yet family firms are unwilling to recruit non-family managers with the required international skills and to dilute their control to obtain the necessary finance. We hypothesize that this argument overlooks the possibility that managers of family-managed SMEs choose business models that both minimize the above-mentioned limitations and leverage the strengths of family governance. Specifically, we argue that selling quality products in global niches allows family-managed SMEs to internationalize without the cosmopolitan managers and the high financial investments required for selling mass-market products abroad; at the same time a global niche business model requires the long time horizon and the high level of social capital that family governance can provide. Modeling a firm’s foreign sales through a gravity model, we test this hypothesis on a large sample of SMEs from four European Union countries. We find that family-managed SMEs have fewer foreign sales than other type of SMEs, but that the difference is partially bridged if family-managed SMEs have adopted a global niche business model.